Analisis Standar Pelayanan Wakaf di Lembaga Roumah Wakaf Surabaya - Meidiana, Meidiana; Sarifudin, Muhammad Farid (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the implementation of waqf service standards at the Roumah Waqf Institution Surabaya. Optimal service standards are an important element in increasing trust and community participation in waqf management. This study uses a qualitative approach with a descriptive design, through document analysis and literature review. The findings show that Roumah Waqf implements various service innovations, including a personal approach to donors, digital services, and waqf asset management policies in accordance with sharia. Factors such as transparency, and responsiveness. In service, it is proven to have a significant impact on the level of community satisfaction. This research contributes to identifying best practices that can be adopted by other waqf institutions in Indonesia, as well as offering strategic recommendations for the development of more professional service standards